A Single Amino Acid Change to Taq DNA Polymerase Enables Faster PCR, Reverse Transcription and Strand-Displacement - Barnes, Wayne M.; Zhang, Zhian; Kermekchiev, Milko B. (Frontiers in Bioengineering and Biotechnology, 2021)
A change of an aspartic acid to asparagine of Taq DNA polymerase is a gain of function mutation that supports faster PCR: the extension times for PCR amplification can be 2-3 times shorter. Surprising results from negative controls led to the discovery of the strand-displacement ability and reverse transcriptase activity of Taq D732N DNA polymerase. We demonstrate that the mutant enzyme can, by itself, catalyze RT-PCR and RT-LAMP assays. Residue 732 is on the surface of the enzyme, not near the active site.